2020
DOI: 10.1136/bmjopen-2019-033405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community pharmacists’ readiness to implement the Falsified Medicines Directive (Directive 2011/62/EC): an English cross-sectional survey with geospatial analysis

Abstract: ObjectivesTo evaluate the readiness to implement the Falsified Medicines Directive (FMD) by community pharmacies in England. Eight secondary objectives were assessed.SettingCommunity/retail pharmacies.ParticipantsWe invited pharmacists from 501 pharmacies to complete a survey. Non-contractors, non-pharmacists or pharmacists practising abroad were excluded. We randomly selected addresses, ensuring that they were nationally representative.InterventionsWe mailed the survey in October 2018 with a single follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This contrasts to a study done by Barrett et al prior to the directive's implementation, which found that 77.5% of English pharmacists surveyed believed the FMD might increase patient safety. 9 While one might hypothesise that this may be due to cultural differences in pharmacy practice, this is a notable contrast between pharmacists' pre-implementation perceptions and post-implementation experiences. In this study, 30.1% of pharmacists indicated that they experienced an increased/greatly increased number of near misses and dispensing errors with the FMD procedures; some pharmacists qualitatively attributed this as one of the reasons for an increased risk to patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts to a study done by Barrett et al prior to the directive's implementation, which found that 77.5% of English pharmacists surveyed believed the FMD might increase patient safety. 9 While one might hypothesise that this may be due to cultural differences in pharmacy practice, this is a notable contrast between pharmacists' pre-implementation perceptions and post-implementation experiences. In this study, 30.1% of pharmacists indicated that they experienced an increased/greatly increased number of near misses and dispensing errors with the FMD procedures; some pharmacists qualitatively attributed this as one of the reasons for an increased risk to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional survey was constructed by the research team, fostered by a comprehensive review of the existing literature 9 , 10 , 11 , 12 , 14 , 15 , 16 , 17 and the research team's experience of working in community pharmacy. During the conduct of the study, KD and KM were pharmacists based primarily in academia, DON was a community pharmacist, and CC was a final year pharmacy student.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper targets the hospital pharmacy supply chain and the impact of the FMD in the dispensing operations. While some of the work in this field relates to problems with FMD implementation or readiness for implementation [ 15 , 16 , 17 , 18 ], our work analyzes the actual supply chain and proposes a new supply chain under the FMD requirements. The case hospital pharmacy supply chain is based in the Austrian Tirol region.…”
Section: The Pharmaceutical Supply Chain: a Hospital Perspectivementioning
confidence: 99%
“…123 The need of specific education of the pharmacist in identifying falsified medicines has been found as a major strategy also in United Kingdom. 157 Additionally, while buyers are often enticed by the possibility of getting the desired drug at a cheaper price, this is rarely the case, due to several "hidden" costs, including shipment, customs clearance, online medical consultations, additional packaging and so forth 112 ; additionally, in the case that no products are received by the buyer, there is little, if any at all, chance to retrieve all money spent. This is, of course, on top of the potential risks associated with sharing payment information on "shady" websites, such as "phishing" and other forms of digital threats.…”
Section: Health Risks Of Unsupervised Use Of Counterfeit Pde5imentioning
confidence: 99%